Pengaruh Kualitas Produk Dan Promosi Terhadap Keputusan Pembelian - Dudung Juhana (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2018)
In recent times, the level of business competition is hugely dynamic and complex. Moreover, the competition is full of uncertainties. It causes the companies to create the competitiveness that can be achieved in creative and innovative ways. One way to support the company profits is the consumer decisions which is caused by the satisfactory product quality and the interactive promotional efforts. This study attempts to determine the effect of product quality and promotion on purchase decisions of distro’s products in Bandung. The distro customers are the samples to prove the hypothesis. The research hypothesis has a significant effect. Thus, it can be said that excellent product quality and interactive promotion lead the consumers to buy distro’s products.